Analysing the influence of companies' green communication in college students' green purchase behaviour: An application of the extended theory of planned behaviour model - Sara Sousa; Elisabete Correia; Clara Viseu; Manuela Larguinho (Administrative Sciences, 2022)
In recent years, there has been a growing concern about the environmental impacts of consumers' behaviour. As this environmental awareness increases, consumers tend to focus more on green products and how purchasing these products represents an effective way to protect the environment. Through the application of the theory of planned behaviour (TPB), in this research, we studied the influence of some key variables on college students' green purchasing behaviour, namely perceived behavioural control, subjective norms, green attitudes, and green purchase intentions. The TPB model was extended to the analysis of the influence of the companies' green communication on students' green purchase behaviour. To achieve the proposed goal, from March to April of 2021, a survey was conducted among the students of a higher education institution (HEI) in Portugal, allowing us to gather 432 valid responses. The findings suggested that all the variables, except the subjective norms, had a positive influence on the students' green purchase intentions. Moreover, it was observed that students' intentions had a positive influence on their green purchase behaviour. This research provides important results not only for policymakers to promote more sustainable behaviours among consumers but also for companies to be more aware of the importance of green communication.
Keywords: 350; college students; green communication; green purchase behaviour; Portugal; theory of planned behaviour